2005
DOI: 10.1063/1.1841466
|View full text |Cite
|
Sign up to set email alerts
|

Effects of buffer layers on the structural and electronic properties of InSb films

Abstract: Effect of material properties on low-energy electron transmission in thin chemical-vapor deposited diamond films J. Appl. Phys. 97, 093717 (2005); 10.1063/1.1893212 Improved pseudomorphic high electron mobility transistor structures on InGaAs substratesWe have investigated the effects of various buffer layers on the structural and electronic properties of n-doped InSb films. We find a significant decrease in room-temperature electron mobility of InSb films grown on low-misfit GaSb buffers, and a significant in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 35 publications
1
28
0
Order By: Relevance
“…Electrons can be scattered by the depletion potential around the dislocations and the lattice dilatation associated with the dislocations. Using the Pödör and Dexter-Seitz models, 20,21 Weng et al 1 found that the dominant factor limiting the electron mobility was the lattice dilatation scattering, which is apparently consistent with the predictions of the Dexter-Seitz model. According to this model, the mobility limited by deformation potential scattering l d is inversely proportional to the edge dislocation density D. These results, therefore, show a quantitative correlation between increasing dislocation density and decreasing electron mobility.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…Electrons can be scattered by the depletion potential around the dislocations and the lattice dilatation associated with the dislocations. Using the Pödör and Dexter-Seitz models, 20,21 Weng et al 1 found that the dominant factor limiting the electron mobility was the lattice dilatation scattering, which is apparently consistent with the predictions of the Dexter-Seitz model. According to this model, the mobility limited by deformation potential scattering l d is inversely proportional to the edge dislocation density D. These results, therefore, show a quantitative correlation between increasing dislocation density and decreasing electron mobility.…”
Section: Resultssupporting
confidence: 66%
“…This highest mobility was higher than the mobilities reported for 2 lm MBE InSb grown directly on GaAs samples done by other groups. 1,22 The samples grown at 350°C and 370°C showed the same carrier concentration at low temperatures (Fig. 2, green and orange curves)-thus the same number of ionized impurities-but markedly different mobilities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The incorporation of InSb/Al x In 1-x Sb interfaces [5,6] and Al x In 1-x Sb/Al y In 1-y Sb interfaces [8,9] in an Al x In 1-x Sb buffer layer is effective in reducing the TD density in an InSb QW [5,6,8,9] and an InSb epilayer [10]. The density of MTs in InSb QWs can be suppressed to an order of 10 2 /cm by the use of 2° off-axis GaAs (001) substrate [7].…”
mentioning
confidence: 98%
“…The barrier layer between the p+ and the absorption layer was grown since it has been reported to block the flow of electrons between the two layers, therefore reducing the diode leakage and allowing operation at higher temperature [16]. The n-contact layer of the InSb photodiode was chosen to be 3 μm thick in order to further reduce the number of defects and threading dislocations, that tend to appear much more frequently near to the interface between the GaSb buffer and the InSb [17]. The InSb materials were etched using a citric acidhydrogen peroxide etchant (33:2:80 C 6 H 8 O 7 :H 2 O 2 :H 2 O by weight) to define the 45 µm diameter active area of the InSb photodiode at a rate of 20 nm/min.…”
Section: Device Fabricationmentioning
confidence: 99%